PKM pelatihan membaca dan menggunakan alat ukur listrik di Mesjid Baiturrahim Kelurahan Bontoduri Kota Makassar - Aminuddin Bakry; Alimuddin Sa’ban Miru (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Mosque in the time of the Prophet Muhammad. The mosque is a very simple building, but its role is very large to be the center of Muslim activities. There Rasulullah SAW prayed five times a day, and in the mosque the Prophet also saw Madinah State and all his friends who became his people, as well as worshipers in his five daily prayers. In the mosque also the Messenger of Allah. giving teachings about Islam, not just the laws of fiqh of worship, but also social, economic, political and state administration issues. Even in the mosque the Messenger of Allah (saw) also received guests and envoys who came from abroad. But unfortunately, today the role of the mosque began to shift. He experienced mutilation of functions and distortion of the work area. The mosque is only synonymous with the place of prayer, nothing more than that. Even more optimal only annual ceremonial events. The prosperity of a mosque is a joy when we see it so easily to find a mosque in Muslim countries. Every village has a mosque, and even in almost every place also provided a mosque. Housing, shops, offices and other public places are almost entirely equipped with a facility called a mosque. Baiturrahim Mosque Pondok Lestari Bontoduri Village has become the center of Muslim activities in congregational prayers, sunnah prayers, halaqah tahfidz, weekly apples, martial arts activities, martial arts, muhadharah, discussions and general studies, seminars, book review, and annual prayers, all of which are activities that make this mosque never quiet. Furthermore, based on observations made on the Baiturrahim mosque youth in relation to PKM, generally there are still many mosque youth who do not yet know how to use and read electrical measuring devices quickly and correctly in the hope of making this mosque a beacon of civilization that gives birth to cadres and interpreters propaganda that is reliable and has knowledge of the theories of electrical measuring devices and the skills of how to use and how to read them. With the addition of knowledge in the form of this training as far as possible a positive contribution to the skills of adolescent mosques themselves.